Role of Delta/Notch-like EGF-related receptor in blood glucose homeostasis - Ruiz-Otero, Nelmari; Kuruvilla, Rejji (Frontiers in Endocrinology, 2023)
Cell-cell interactions are necessary for optimal endocrine functions in the pancreas. β-cells, characterized by the expression and secretion of the hormone insulin, are a major constituent of functional micro-organs in the pancreas known as islets of Langerhans. Cell-cell contacts between β-cells are required to regulate insulin production and glucose-stimulated insulin secretion, which are key determinants of blood glucose homeostasis. Contact-dependent interactions between β-cells are mediated by gap junctions and cell adhesion molecules such as E-cadherin and N-CAM. Recent genome-wide studies have implicated Delta/Notch-like EGF-related receptor (Dner) as a potential susceptibility locus for Type 2 Diabetes in humans. DNER is a transmembrane protein and a proposed Notch ligand. DNER has been implicated in neuron-glia development and cell-cell interactions. Studies herein demonstrate that DNER is expressed in β-cells with an onset during early postnatal life and sustained throughout adulthood in mice. DNER loss in adult β-cells in mice (β-Dner cKO mice) disrupted islet architecture and decreased the expression of N-CAM and E-cadherin. β-Dner cKO mice also exhibited impaired glucose tolerance, defects in glucose- and KCl-induced insulin secretion, and decreased insulin sensitivity. Together, these studies suggest that DNER plays a crucial role in mediating islet cell-cell interactions and glucose homeostasis.